The Contemporary Maqāṣid Sharia Perspective on Sexual Violence Provisions in the Indonesian Law Number 12 Year 2022 - Muhammad Iqbal Juliansyahzen; Ocktoberrinsyah (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
The problem of sexual violence is in the spotlight of various groups because it has a multidimensional impact. Various efforts have been made to guarantee and protect the rights of victims. One of these efforts is the presence of Law Number 12 of 2022 concerning the Crime of Sexual Violence. This study aims to analyze the substance of the law and its compatibility with Sharia principles. This type of research is qualitative with a juridical-philosophical approach with the Jasser Auda’s perspective on Maqāṣid Sharia. The content analysis (content-analysis) is used to examine the content of the law in depth and its suitability with the theory. This study concludes that the concept of sexual violence contained in Law 12 of 2022 is in accordance with Maqāṣid Sharia, mainly in six respects, namely ḥifẓ al-dīn (the preservation of religion), ḥifẓ al-nafs (the preservation of the soul), ḥifẓ al’aql (the preservation of mind), ḥifẓ al-nasl (the preservation of offspring), ḥifẓ al-māl (the preservation of property), and ḥifẓ al-‘irḍ (the preservation of honor). This is based on the basic principles of Maqāsid Sharia which emphasizes morality, openness, development, humanity, and human rights.